2020
DOI: 10.3390/ijerph17176269
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Markers of Oxidative Stress and α-Amylase in Saliva of Children Associated with a Tennis Competition

Abstract: The purpose of this paper was to analyze the changes caused by a one-day tennis tournament in biomarkers of oxidative stress and α-amylase in saliva in children. The sample was 20 male active children with the following characteristics: (a) age of players = 9.46 ± 0.66 years; (b) weight = 34.8 ± 6.5 kg; (c) height = 136.0 ± 7.9 cm; (d) mean weekly training tennis = 2.9 ± 1.0 h. The tennis competition ran for one day, with four matches for each player. Data were taken from the average duration per match and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…To our current understanding, there is a limited body of literature addressing alterations in the salivary oxidative status in response to purely short-term acute psychological stress. In a prior study, it was observed that the salivary antioxidant levels in children, assessed using a variety of parameters, exhibited an increase prior to a tennis competition, and this increase was linked to psychological stress [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our current understanding, there is a limited body of literature addressing alterations in the salivary oxidative status in response to purely short-term acute psychological stress. In a prior study, it was observed that the salivary antioxidant levels in children, assessed using a variety of parameters, exhibited an increase prior to a tennis competition, and this increase was linked to psychological stress [44].…”
Section: Discussionmentioning
confidence: 99%
“…The score range for both the STAI-T subscale and the STAI-S subscale falls between 20 (minimum) and 80 (maximum). STAI scores are commonly categorized as follows: "low or no anxiety" (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37), "moderate anxiety" (38)(39)(40)(41)(42)(43)(44), and "high anxiety" (45-80) [26,27].…”
Section: Assessment Of Stress Levelmentioning
confidence: 99%
“…To the best of our knowledge, no publications are dealing with the changes in salivary oxidative status and “pure” and short-term acutely applied psychological stress. In a previous study, the salivary antioxidant status of children, estimated through a panel of different parameters, was found to be increased prior to a tennis completion, which was associated with psychological stress [ 31 ]. It was shown that an exam, as a stimulus for psychological stress, causes an increase in salivary antioxidant status, while diminishes the oxidant counterpart [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, serum has been traditionally used to evaluate changes in the oxidative status of patients with different thyroidal diseases [14][15][16][17]. However, saliva is an easy-to-obtain, stress-free sample that has been used for the study of different biomarkers in other diseases and species [18][19][20][21][22]. To the author's knowledge, the oxidative status has not been evaluated in serum and saliva of dogs with hypothyroidism previously.…”
Section: Introductionmentioning
confidence: 99%